One Health approach: A platform for intervention in emerging public health challenges of Kerala state - A. Sukumaran; A. S. Pradeepkumar (International Journal of One Health, 2015)
The authors, key functionaries in the Kerala state public health system, review the communicable disease scenario of the state for the past 4 years, and in the background of the One Health concept, opines that the re-emerged discipline is perfectly in tune with the current challenges of the state. The unique model of Kerala state is witnessing newer challenges in its public health arena: The rapidly increasing migrant workforce from relatively poorer states of India, rapid urbanization and its consequent stress on public health, unsolved issues of urban waste disposal, reemergence of many communicable diseases like malaria, more so, the falciparum type, emergence of many zoonotic diseases like Lyme disease, scrub typhus, and Kyasanur forest disease etc. Conventional zoonotic infections such as anthrax and brucellosis remain potential threat for human health as well. Rabies continued to cause major concern from mortality point of view, as well as major drainer of state’s budget every year. Leptospirosis has remained major burden among the communicable disease for the past 10 years, and the annual incidence ranged from 2 to 7 per 100,000 population. Having a large section of its people working in various agriculture and animal rearing occupations, the state has all risk factors for propagation of Leptospirosis, but lacks interdisciplinary collaboration in its control and prevention area, the author highlights major avenues for collaboration. Japanese encephalitis appeared as an epidemic in 2011 in two of the southern districts in Kerala, one of the districts being famous tourist spot for both humans, as well as migrant birds. There is ample scope for collaborative research on the source of the virus, and in the subsequent years, the disease had been detected in more districts. Lyme disease was reported for the first time in India, from one of the districts in Kerala, promptly investigated by a joint team from Human Public Health and Veterinary Public Health institutions in 2013, reiterating the role of interdisciplinary collaboration in outbreak investigations. Influenza had been evolving rapidly in the state from the seasonal type earlier, to H1N1 since past few years, now poised for an emergence of MERS Corona and still expected are the more fatal and highly pathogenic types. The migratory bird-pig-domestic birds-human interface being a well-knit network in the state is most suitable for all new variant s of influenza virus evolution. Outbreaks of these infectious diseases need investigations by combined teams from departments such as Human Health, Animal Health, and Wild Life. The One Health concept thus becomes appropriate to address such an eventuality. The authors have concluded by identifying the probable avenues for collaborative works in addressing the public health challenges of Kerala state, India.